Bauran Pemasaran dalam Menawarkan Kursus di Wall Street English - Ariya Hidayattulloh Natakusumah; Anne Ratnasaria (UNISBA Press, 2023)
Abstract. Indonesian has been at the low rank in terms of English Proficiency since 2017 and still remains below the ranks of other ASEAN countries, such as Singapore with (68.63) the highest level of proficiency, then followed by the Philippines (61.84) and Malaysia (58.32). Indonesian ranks even lower than Vietnam (53.12) which is medium level of proficiency. The purpose of this study is to determine marketing strategies used by Wall Street English Dago to its members in Bandung. There are seven main variables of this marketing mix, namely product, price, place, promotion, people, process, and physical environment.Research results for the marketing mix offering the English class of Wall Street is in the very good category with a total rating of 85.83%. This demonstrates that Wall Street English has created a marketing mix that is consistent with the wishes and needs of consumers, such as: (1) Easy to access multimedia classes, 2. The results obtained are in line with customer investment, (3) Wall Street English Dago has a modern design that is comfortable to learn for its members, the mentors offer special info about the event to the members clearly, (4) Wall Street English Dago staff offer gracious and friendly service, (5) Wall Street English Dago's learning process helps improve its members' language skills, (6) Clean environment of Wall Street English Dago is very well maintained. Abstrak. Bahasa Indonesia berada di peringkat rendah dalam hal Kecakapan Bahasa Inggris sejak tahun 2017 dan masih berada di bawah peringkat negara-negara ASEAN lainnya, seperti Singapura dengan (68,63) tingkat kemahiran tertinggi, kemudian diikuti oleh Filipina (61,84) dan Malaysia (58,32). ). Peringkat Indonesia bahkan lebih rendah dari Vietnam (53,12) yang merupakan tingkat kemahiran menengah. Tujuan dari penelitian ini adalah untuk mengetahui strategi pemasaran yang digunakan oleh Wall Street English Dago kepada anggotanya di Bandung. Ada tujuh variabel utama dari bauran pemasaran ini, yaitu produk, harga, tempat, promosi, orang, proses, dan lingkungan fisik. Hasil penelitian untuk penawaran bauran pemasaran kelas bahasa Inggris Wall Street berada pada kategori sangat baik dengan total peringkat sebesar 85,83%. Hal ini menunjukkan bahwa Wall Street English telah menciptakan bauran pemasaran yang sesuai dengan keinginan dan kebutuhan konsumen, seperti: (1) Kelas multimedia yang mudah diakses, 2. Hasil yang diperoleh sesuai dengan investasi pelanggan, (3) Wall Street English Street English Dago memiliki desain modern yang nyaman untuk dipelajari bagi para anggotanya, para mentor memberikan info khusus tentang acara tersebut kepada para anggota dengan jelas, (4) Staf Wall Street English Dago menawarkan layanan yang ramah dan bersahabat, (5) Wall Street English Dago's proses pembelajaran membantu meningkatkan kemampuan bahasa anggotanya, (6) Lingkungan bersih Wall Street English Dago sangat terjaga.